The analysis of risk and return using Sharia compliance assets pricing model with profit-sharing approach (Mudharabah) in energy sector company in Indonesia - Ahmad Faisol; Sulaeman Rahman Nidar; Aldrin Herwany (Journal of Risk and Financial Management, 2022)
This study aimed to examine the relationship between risk and return using the Sharia Compliant Assets Pricing Model (SCAPM) with the profit-sharing approach (mudharabah) variable as a substitute for the risk-free rate (Rf) in energy sector companies in Indonesia as an empirical test object. The analytical tool used is univariate time series analysis using the ARX-GARCH model to determine validity of the model and forecast for the next 7 days. The findings showed a significant relationship between risk and return in a mining company in Indonesia. In addition, in terms of stock volatility, which is higher than market volatility, the shares of mining companies are shown to be in demand by investors compared to other average stocks in the Indonesian market. So, it can be concluded that the mudharabah variable can be used as a risk-free alternative rate (Rf).
Keywords: 650; sharia compliance asset pricing; profit-sharing approach; ARX-GARCH model